2001
DOI: 10.1016/s0955-0674(00)00180-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral transport and the cytoskeleton

Abstract: In the past decade, studies into the way in which intracellular bacterial pathogens hijack and subvert their hosts have provided many important insights into regulation of the actin cytoskeleton and cell motility, in addition to increasing our understanding of the infection process. Viral pathogens, however, may ultimately unlock more cellular secrets as they are even more dependent on their hosts during their life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 83 publications
2
107
0
1
Order By: Relevance
“…Several bacteria and viruses have been shown to subvert the cytoskeleton for their intracellular trafficking (Dramsi and Cossart, 1998;Frischknecht and Way, 2001;Ploubidou and Way, 2001;Sodeik, 2000). However, despite a growing body of knowledge accumulating in this field, how retroviruses reach the nucleus of the newly infected cell is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several bacteria and viruses have been shown to subvert the cytoskeleton for their intracellular trafficking (Dramsi and Cossart, 1998;Frischknecht and Way, 2001;Ploubidou and Way, 2001;Sodeik, 2000). However, despite a growing body of knowledge accumulating in this field, how retroviruses reach the nucleus of the newly infected cell is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented that some enveloped viruses induce the formation of diverse actin structures to facilitate their internalization into host cells (Cudmore et al, 1997;Higley & Way, 1997;Ploubidou & Way, 2001;Chu et al, 2003Chu et al, , 2006Eash & Atwood, 2005). Viral particles of murine leukemia virus induce actin reorganization to form filopodia to which viruses have been reported to associate before cell infection (Lehmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, once viruses enter cells they require cytoplasmic transport to reach specific subcellular sites for replication and egress. Numerous studies have revealed that retrograde and anterograde transport of animal viruses is supported by MTs and their associated proteins (14,15,73,74), and an increasing number of viral proteins that interact with MTs or MAPs have begun to be identified (Table 1). Virus-MAP interactions, be they functional or physical, can promote virus trafficking in an infected cell, by directly facilitating latching on of virus particles to cytoskeletal tracks, or modifying MT dynamics to optimize movement along the tracks.…”
Section: Promotion Of Viral Trafficking By Mapsmentioning
confidence: 99%